Celiac Arterioenteric Fistula after Open Repair of Celiac Artery Aneurysm - Case Report - Arpit Amin; Saptarshi Biswas; Francis Carroll; Romeo Mateo; Sateesh Babu (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2015)
In a patient with a known history of aortic surgery, presence of upper gastrointestinal bleeding requires a high index suspicion for the possibility of aorto-enteric fistula. Aorto-enteric fistula is an uncommon but known complication occurring after abdominal aortic reconstruction. However, there are few reported cases of enteric fistulas arising after splanchnic artery aneurysm repair. We report a unique case of a celiac artery graft - duodenal fistula in a 60-year-old male, who developed upper gastrointestinal bleeding two months after initial open resection of a celiac artery aneurysm and placement of an aorto-celiac artery graft. The patient underwent successful repair of the fistula and the resection of the involved graft with ligation of the common hepatic artery and splenectomy. Our case report highlights the rare entity of celiac arterio-enteric fistula after open repair of a celiac artery aneurysm and reviews the diagnostic and treatment modalities available for successful management of this rare complication.